Balancing Efficiency and Quality: Effects of Gradual Temperature Increase on Extra Virgin Olive Oil Extraction - Giulia Angeloni; Agnese Spadi; Ferdinando Corti; Luca Calamai; Piernicola Masella; Alessandro Parenti (AgriEngineering)
This study examined the influence of malaxation temperatures on the extraction of extra virgin olive oil (EVOO) and its phenolic compound content, aiming to balance energy efficiency with final product quality. Extraction was tested at three temperatures of malaxation, 21 °C, 27 °C, and a gradual increase from 21 °C to 27 °C. Higher malaxation temperatures improved extraction yields and phenolic compounds. However, a gradual temperature increase produced promising results. The research found that yields like those obtained at 27 °C could be achieved using a lowered temperature of up to 6 °C for 15 min. The gradual temperature increase resulted in a 15% increase in phenolic compounds in comparison to low temperature extracted samples. The presence of beneficial aromatic compounds, such as (E)-2-hexenal, increased with higher temperatures, enhancing the fresh and fruity sensory notes of the oil. However, compounds linked to sensory defects, such as (E)-2-heptenal, increased at higher temperatures, indicating a need for careful modulation of extraction temperatures. In conclusion, adopting a gradually increasing temperature profile during malaxation represents an advantageous strategy for optimizing EVOO extraction, improving both the quality of the final product and operational efficiency, thus contributing to more sustainable and economical production.